Teacher Assistance in Improving the Quality of Students' Al-Qur'an Reading through Tajweed Learning - Luluk Atirotu Zahroh (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
Studying recitation is the basis for improving recitation when studying the Qur'an. Recitation as a foundation causes recitation of recitation done first before people learn the Qur'an in more detail or usually in line with learning the Qur'an itself. Studying recitation is helpful to improve the quality of reading the Qur’an, both in sound and rhythm, but the most urgent is to justify the meaning. The need for the recitation of recitation is significant because it is used to improve children's reading of the Qur'an, especially regarding the law of nun and tanwin, and mad reading. Therefore, so that children quickly learn the Qur’an, especially in terms of reading the Qur’an, TPQ must learn the knowledge of recitation to children. Tajweed material includes the rules of reading the Qur’an, among others: Makhraj Letter Hijaiyah, Provisions Qalqalah, Provisions Nun and Mim Musyaddadah (Tasydid), Provisions Lam Letters, Provisions of the Sukun, Provisions of Ikhfa, Provisions of Izhhar, Provisions of Qalqalah, Provisions on Nun and Mim Musyaddadah (Tasydid), Provisions on Ra Letter, Mad Provisions, Provisions on Alif and Lam Syamsiyah Letters, Provisions on Alif and Lam Qamariyah Letters, Waqaf Provisions, and Sajadah Verses; 2) The step of recitation is done by the cleric first reading a short verse, for example, a sentence in a poem that is long enough to a certain waqaf then the students follow it simultaneously. After that, one by one, the students were allowed to read what had been said simultaneously. If there is an error in the pronunciation, mainly from the perspective of recitation, it is immediately reprimanded and justified; 3) The strategies adopted include: having a mature and strategic education plan and having a learning curriculum that includes: 1) The existence of clear learning objectives 2) The existence of suitable learning methods and techniques and is applied continuously with various innovations and evaluations 3 ) The existence of a material or teaching material that is representative and by the learning objectives 4) The existence of a professional teacher in the field of learning the Qur'an.